The Isolation of Staphylococcus Epidermidis Bacteria in White Snapper Salted Fish (Lates Calcalifer) of Sibolga City, North Sumatera Province - Lestari, Rafika; Admi, Masda; Rastina, Rastina; Dewi, Maryulia; Nurliana, Nurliana; Harris, Abdul; Riady, Ginta (Universitas Teuku Umar, 2020)
Salted fish is vulnerable to contamination by microbial. Staphylococcus epidermidis is one of the bacteria that can contaminate the salted fish. This research aims to isolate the Staphylococcus epidermidis bacteria contamination in salted white snapper fish sold in Sibolga City, North Sumatra Province. The sample used was white snapper salted fish, amounting to 10 samples from 10 traders. The isolation of Staphylococcus epidermidis was carried out using the Carter method. White snapper salted fish are mashed using a blender, then planted on Nutrient Broth (NB) as a bacterial growth media. Furthermore, identification of bacterial colonies grew using gram staining, Manitol Salt Agar (MSA) media, Blood Agar Plate (BAP) media, catalase test and confectionery media (Manitol and Glucose). The data obtained were analyzed descriptively. The results of this study suggest that Staphylococcus epidermidis contains bacterial contamination. Based on the data collected, it can be concluded that 7 out of 10 samples of white snapper salted fish sold in Sibolga City, North Sumatra Province, are contaminated with 70 percent Staphylococcus epidermidis bacteria.